Radial stability of periodic orbits of damped Keplerian-like systems. (August 2020) - Liang, Zaitao; Liao, Fangfang
Abstract: In this paper, by using the third order approximation method, the averaging method and the theory of upper and lower solutions, we study the existence and radial stability of periodic orbits of damped Keplerian-like systems. Two different results are obtained: perturbative and global results. Our results are also applicable to the classical Keplerian-like systems.